Urban Markets in Lagos, Nigeria. Issue 7 (15th July 2013) - Ikioda, Faith Ossy
Abstract An emerging body of work on farmers markets and other traditional retail markets has recently come into focus among scholars concerned with the study of contemporary retailing and consumption practices. Marketplaces in Euro‐American contexts are currently promoted as essential elements of urban renaissance, promoting local food movements, tourism and economic regeneration and encouraging face‐to‐face interactions among increasingly diverse ethnic groups in towns and cities. At the same time, the study of marketplaces which has long been of interest to scholars working in the global south is primarily portrayed through a lens of developmentalism as archaic and embroiled in a narrative about the poverty of traders and urban informality, thus limiting the latter's contributions to the critical retailing and consumption literature. This paper explores the case of marketplaces in Lagos, Nigeria, to comments on the challenges and possibilities for making meaningful comparative research that connect marketplaces across the global north–south divide.